Education Management StrategyIn Improving the Quality of Learning in the Digital Era - Legi, Hendrik; Legi, Devarsh Gevariel Dean; Giban, Yoel (Multidisciplinary Journal of Education , Economic and Culture, 2026)
Digital transformation in the world of education has brought significant changes in learning methods and governance of educational institutions. This research aims to analyze education management strategies in improving the quality of learning in the digital era and identify challenges and solutions in its implementation. The method used in this study is a literature study, by examining various scientific sources, journals, books, and policy reports related to education digitalization. The research steps include (1) identification and selection of relevant literature, (2) analysis of digital education management concepts and theories, (3) evaluation of challenges and opportunities for technology implementation in education, and (4) preparation of recommendations for digital-based education management strategies. The results of the study show that the success of education management in the digital era is influenced by leadership factors, infrastructure, readiness of educators, and educational policies that support technological innovation. The benefits of this research are expected to provide insights for educational institutions in developing effective management strategies, assisting educators in adopting technology-based learning methods, and providing input for the government in formulating inclusive and sustainable digital education policies. This study shows that the application of technology in education management is able to increase the effectiveness of the learning process, administrative efficiency, and active participation of students in academic activities. Therefore, education managers must implement the right management strategies in order to create an effective, innovative, and in accordance with the demands of the times.